Recurrent estimates for Kebbi State, 1995. - Kebbi State Government (Nigeria); Kebbi State Government, Nigeria (Birnin Kebbi : Kebbi State Government, Nigeria, 1992)
This is the approved estimates and budget for capital and recurrent expenditure for Kebbi State, Nigeria for 1995.
lje 15/3/2019
Arch.
Keywords: Budget; Expenditures, Public; Kebbi State (Nigeria); Nigeria